2006
DOI: 10.1111/j.0909-725x.2006.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive skin: correlation with skin surface microrelief appearance

Abstract: Sensitive skin is common in the healthy population. ISI can contribute towards the identification of subjects with sensitive skin and the development of more specific skin treatments for this prevalent condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…The skin of stingers with self-reported sensitive skin appears to be rougher since fast Fourier transform evaluation of tapes after tape-stripping the stratum corneum in 243 stingers revealed a lower content of cells. This implies a more irregular and rougher [57], possibly less hydrated, skin. However, objectively measured skin elasticity and distensibility show no correlation with hypersensitivity [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin of stingers with self-reported sensitive skin appears to be rougher since fast Fourier transform evaluation of tapes after tape-stripping the stratum corneum in 243 stingers revealed a lower content of cells. This implies a more irregular and rougher [57], possibly less hydrated, skin. However, objectively measured skin elasticity and distensibility show no correlation with hypersensitivity [54].…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with sensitive skin frequently report reddening of their skin [15,35,37,38,43,44,49,57,58]. Therefore, the assessment of erythema in skin irritation has been widely investigated, either by visual assessment [28,37,41,59,60] or by quantitative methods such as tristimulus reflectance colorimetry (a* value) [20,50,51,52], reflectance spectrophotometry (erythema index) [38,53,59] or laser Doppler flowmetry (cutaneous blood flow) [20,41,48,50,51,53,61].…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this, Sparavigna et al . observed a correlation ( r = 0·46, P < 0·01) between stinging intensity and irregularity skin index, implying a rougher skin in SS …”
Section: Antibody Specificationsmentioning
confidence: 86%
“…21 In agreement with this, Sparavigna et al observed a correlation (r = 0Á46, P < 0Á01) between stinging intensity and irregularity skin index, implying a rougher skin in SS. 22 Vascular reactivity seems to play a role in the pathomechanism. The strong spongiosis in the SS group might explain the relative decrease of Ki67+ cells per mm BM at 24 h, which has also been observed in other studies.…”
mentioning
confidence: 99%
“…Bei sensitiver Haut wurde weiterhin eine Verdünnung des Stratum corneum gemessen [1], die mit der Barrierefunktion korreliert. Zudem zeigte sich ein verändertes Oberflächenmikrore-lief [25], was ebenfalls mit einer gestörten Barriere korreliert. Zudem wird ein Zusammenhang mit verschiedenen Hautzuständen und Hauterkrankung berichtet, bei denen ebenfalls eine gestörte Barriere vorliegt (trockene Haut, atopisches Ekzem, seborrhoisches Ekzem, Acne vulgaris, Rosazea, periorale Dermatitis).…”
Section: Reaktionsmechanismenunclassified